Alternative NF-κB signaling promotes colorectal tumorigenesis through transcriptionally upregulating Bcl-3. Issue 44 (1st November 2018) - Tao, Yu; Liu, Zhanjie; Hou, Yingyong; Wang, Shouli; Liu, Sanhong; Jiang, Yuhang; Tan, Dan; Ge, Qiulin; Li, Cuifeng; Hu, Yiming; Liu, Zhi; Chen, Xi; et al.
Abstract Multiple studies have shown that chronic inflammation is closely related to the occurrence and development of colorectal cancer (CRC). Classical NF-κB signaling, the key factor in controlling inflammation, has been found to be of great importance to CRC development. However, the role of alternative NF-κB signaling in CRC is still elusive. Here, we found aberrant constitutive activation of alternative NF-κB signaling both in CRC tissue and CRC cells. Knockdown of RelB downregulates c-Myc and upregulates p27Kip1 protein level, which inhibits CRC cell proliferation and retards CRC xenograft growth. Conversely, overexpression of RelB increases proliferation of CRC cells. In addition, we revealed a significant correlation between Bcl-3 and RelB in CRC tissues. The expression of RelB was consistent with the expression of Bcl-3 and the phosphorylation of Bcl-3 downstream proteins p-Akt (S473) and p-GSK3β (S9). Bcl-3 overexpression can restore the phenotype changes caused by RelB knockdown. Importantly, we demonstrated that alternative NF-κB transcriptional factor (p52:RelB) can directly bind to the promoter region ofBcl-3 gene and upregulate its transcription. Moreover, the expression of RelB, NF-κB2 p52, and Bcl-3 was associated with poor survival of CRC patients. Taken together, these results represent that alternative NF-κB signaling may function as an oncogenic driver in CRC, and also provide new ideas and research directions for the pathogenesis, prevention, and treatment of other inflammatory-related diseases.